2020
DOI: 10.1111/nph.16702
|View full text |Cite
|
Sign up to set email alerts
|

When and where soil is important to modify the carbon and water economy of leaves

Abstract: Summary Photosynthetic ‘least‐cost’ theory posits that the optimal trait combination for a given environment is that where the summed costs of photosynthetic water and nutrient acquisition/use are minimised. The effects of soil water and nutrient availability on photosynthesis should be stronger as climate‐related costs for both resources increase. Two independent datasets of photosynthetic traits, Globamax (1509 species, 288 sites) and Glob13C (3645 species, 594 sites), were used to quantify biophysical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 91 publications
10
50
2
Order By: Relevance
“…Specifically, plants in the ambient treatment adopted a resource conservative strategy (low nitrogen concentration and specific leaf area) 9 . We also find evidence that plants in the Alliaria ambient treatment had a higher cost of nitrogen uptake than plants in the Alliaria weeded treatment, as indicated by the greater PNUE and lower ratio of N area to g s , consistent with previous results across nutrient availability gradients 32 . For one native species, Arisaema, there was evidence of differential trait investment that increased PNUE and decreased WUE, as would be expected if nutrient availability was more impacted than water availability by Alliaria invasion (Figure 2) 30 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Specifically, plants in the ambient treatment adopted a resource conservative strategy (low nitrogen concentration and specific leaf area) 9 . We also find evidence that plants in the Alliaria ambient treatment had a higher cost of nitrogen uptake than plants in the Alliaria weeded treatment, as indicated by the greater PNUE and lower ratio of N area to g s , consistent with previous results across nutrient availability gradients 32 . For one native species, Arisaema, there was evidence of differential trait investment that increased PNUE and decreased WUE, as would be expected if nutrient availability was more impacted than water availability by Alliaria invasion (Figure 2) 30 .…”
Section: Discussionsupporting
confidence: 90%
“…We also found that plants in the ambient treatment adopted a resource conservative strategy (reduced specific leaf area) (Funk 2013). Together, these results are consistent with previous plant physiology responses across nutrient availability gradients (Paillassa et al 2020), and support, for the first time, the hypothesis that invasion-induced changes in native plant traits are generated by mutualism disruption and reduced soil resource provisioning. In other words, because of the reduction in nutrient availability by Alliaria, native plants in these plots are increasing their relative water use to maintain photosynthesis at lower relative nutrient use.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, plants in the ambient treatment adopted a resource conservative strategy (low nitrogen concentration and specific leaf area) 9 . We also find evidence that plants in the Alliaria ambient treatment had a higher cost of nitrogen uptake than plants in the Alliaria weeded treatment, as indicated by the greater PNUE and lower ratio of N area to g s , consistent with previous results across nutrient availability gradients 32 . For one native species, Arisaema, there was evidence of differential trait investment that increased PNUE and decreased WUE, as would be expected if nutrient availability was more impacted than water availability by Alliaria invasion (Figure 2) 30 .…”
Section: Discussionsupporting
confidence: 90%
“…Third, the diurnal course of the photosynthetic rate depends not only on light but also on other environmental factors (i.e., humidity, temperature, VPD, etc.) [42,109,110] in addition to whole-plant water availability [4,[111][112][113][114][115]. Therefore, the effect of midday depression due to stomatal closure [60,110,112,115] and photoinhibition [60,112] also would significantly alter the daily carbon gain of leaves.…”
Section: Morphological Acclimationmentioning
confidence: 99%